2022
DOI: 10.1136/heartjnl-2021-320501
|View full text |Cite
|
Sign up to set email alerts
|

Mixed aortic stenosis and regurgitation: a clinical conundrum

Abstract: Mixed aortic stenosis (AS) and aortic regurgitation (AR) is the most frequent concomitant valve disease worldwide and represents a heterogeneous population ranging from mild AS with severe AR to mild AR with severe AS. About 6.8% of patients with at least moderate AS will also have moderate or greater AR, and 17.9% of patients with at least moderate AR will suffer from moderate or greater AS. Interest in mixed AS/AR has increased, with studies demonstrating that patients with moderate mixed AS/AR have similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In current guidelines and clinical practice, interventions for such patients are generally based on the predominant lesions 4,5 . Some scholars have suggested that the current approach to managing patients based on their primary lesions may be too crude, because this approach may underestimate the true hemodynamic impact of combined lesions, 6 as the coexistence of pressure and volume overload can lead to unique cardiac pathological changes 7,8 . And the results between the limited previous studies about the severe AS patients with more than moderate AR are contradictory 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In current guidelines and clinical practice, interventions for such patients are generally based on the predominant lesions 4,5 . Some scholars have suggested that the current approach to managing patients based on their primary lesions may be too crude, because this approach may underestimate the true hemodynamic impact of combined lesions, 6 as the coexistence of pressure and volume overload can lead to unique cardiac pathological changes 7,8 . And the results between the limited previous studies about the severe AS patients with more than moderate AR are contradictory 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…And the results between the limited previous studies about the severe AS patients with more than moderate AR are contradictory 9,10 . Therefore, a new perspective is needed to assess the value of TAVR for this cohort of patients 8 . As we all know, the recovery of left ventricular morphology and cardiac function in patients after TAVR is decisive for long‐term prognosis 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another clinical conundrum in management of adults with AS is the problem of combined stenosis and regurgitation of the aortic valve. Nedadur and colleagues8 provide a detailed review of the epidemiology, physiology and clinical outcomes for mixed AS and aortic regurgitation including an overview of the diagnostic approach and summary of current guidelines for timing and choice of intervention.…”
mentioning
confidence: 99%